Larger patients shouldn’t have fewer options: urethroplasty is safe in the obese - Alger, Jordan (Int Braz J Urol, 2020)
OBJECTIVE: To examine the impact of obesity on perioperative outcomes and urethral stricture recurrence after anterior urethroplasty. MATERIAL AND METHODS: We reviewed our prospectively maintained single-surgeon database to identify men with anterior urethral strictures who had undergone anastomotic or augmentation urethroplasty between October 2012 and March 2018. In all, 210 patients were included for primary analysis of perioperative outcomes, while 193 patients with at least 12 months follow-up were included for secondary analysis of stricture recurrence. Patients grouped by BMI were compared using univariate and multivariate analyses for perioperative outcomes and log rank testing for recurrence-free survival. RESULTS: Overall, 41% (n=86) of patients were obese and 58.6% (n=123) had bulbar urethral strictures. Obese patients had significantly longer urethral strictures (mean=6.7cm±4.7) than nonobese patients (p <0.001). Though urethroplasty in obese patients was associated with increased estimated blood loss (EBL) relative to normal BMI patients on both univariate (p=0.003) and multivariate (p <0.001) analyses, there was no difference in operative time, length of stay, or complication rate between BMI groups. At a mean follow-up interval of 36.7 months, 15% (n=29) of patients had stricture recurrence, yet recurrence-free survival was not significantly different between groups (log rank p=0.299). Dorsal augmentation urethroplasty resulted in significantly fewer recurrences in obese patients compared to nonobese patients (p=0.036). CONCLUSION: Despite the association with increased urethral stricture length and EBL, obesity is not predictive of adverse perioperative outcomes or stricture recurrence. Obese patients should be offered urethral reconstruction, but patient selection and preoperative counseling remain imperative.